Prácticas sociales que dinamizan la resolución de problemas matemáticos. - Daza Garzón, Diana Yiseth; González Arenas, Gloria Lucía; Rodríguez Báez, Jully Andrea (Universidad Pedagógica y Tecnológica de Colombia, 2022)
This article presents social practices as an ally in the dynamization of mathematical problem solving inside and outside the classroom, with students from the rural sector, opening the possibility of a new learning perspective based on the student’s lived experiences within their context. It shows a view of how rural education is seen, the educational practices and how these are related to mathematics. It also recognizes teaching practices as the scenario in which research processes that contribute to the development of mathematical, critical and reflective thinking of students are generated; where the teacher becomes a mediator in the teaching and learning process that rescues the daily life experiences of each of the participants of the educational encounters. This document is the result of a social investigation that arises from the identification of a situation with the objective of promoting diverse social practices and through different sources to analyze those aspects that allow to raise practices that favor learning; then to raise those social practices as generators of investigative processes and to arrive to present a reflection around the teaching practices as a contribution to the resolution of mathematical problems.